2010
DOI: 10.1002/vnl.20240
|View full text |Cite
|
Sign up to set email alerts
|

Organo bifunctional silane effects on the vibration, thermal, and mechanical properties of a vinyl‐group‐containing silicone rubber/natural rubber/silica compound

Abstract: A bifunctional silane (TESPD) was added to a vinylgroup-containing silicone rubber (SR)/natural rubber (NR)/silica compound, and the resulting mechanical, morphological, and thermal properties were compared with those of an NR/silica compound. The addition of TESPD to the silica-filled SR/NR compound formed an SR-silane-silica-silane-NR structure that behaved as a ter-polymer. The addition of SR into the NR improved the mechanical properties (torque maximum, modulus, elongation at break, and hardness) and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Silicone rubber is the one most widely used as a biocompatible rubber as well as in blending with other polymers . The applications of silicone rubber include houseware items (toys, computer keyboards, phone keypads, ear plugs, ear phones, and watches) that are likely to contact the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Silicone rubber is the one most widely used as a biocompatible rubber as well as in blending with other polymers . The applications of silicone rubber include houseware items (toys, computer keyboards, phone keypads, ear plugs, ear phones, and watches) that are likely to contact the human body.…”
Section: Introductionmentioning
confidence: 99%
“…One more conclusion may be drawn for the NR/SR blends based on the appearance of a new peak, when the compatibilizer B or C was added. These peaks should belong to the interface layer , and it represented a partial miscibility between the NR and the SR . It was also found that the new peak of the blends with compatibilizer C (−93.00°C) was much lower than that of blends with compatibilizer B (−85.62°C).…”
Section: Resultsmentioning
confidence: 91%
“…Current studies on this field are very limited because of the large difference in solubility between NR and SR (δ NR = 8.15 cal 1/2 cm −3/2 ; δ SR = 7.30 cal 1/2 cm −3/2 ) . This large difference results in poor performance of the blending system, even leading to the separation of the two phases.…”
Section: Introductionmentioning
confidence: 99%
“…Ceramic silicone rubber composites with a polymeric matrix are widely used in thermal protection systems for space vehicles and civilian electrical equipments, owing to its good ablation resistance, low cost, low density, and high electrical insulation properties. Silicone rubber–based ceramic composite is a heat insulation material for wire and cable insulation coating material .…”
Section: Introductionmentioning
confidence: 99%